GPR40 activation initiates store-operated Ca2+ entry and potentiates insulin secretion via the IP3R1/STIM1/Orai1 pathway in pancreatic β-cells - Usui, Ryota; Yabe, Daisuke; Fauzi, Muhammad; Goto, Hisanori; Botagarova, Ainur; Tokumoto, Shinsuke; Tatsuoka, Hisato; Tahara, Yumiko; Kobayashi, Shizuka; Manabe, Toshiya; Baba, Yoshihiro; Kurosaki, Tomohiro; et al. (Scientific reports, 2019)
The long-chain fatty acid receptor GPR40 plays an important role in potentiation of glucose-induced insulin secretion (GIIS) from pancreatic β-cells. Previous studies demonstrated that GPR40 activation enhances Ca 2+ release from the endoplasmic reticulum (ER) by activating inositol 1,4,5-triphosphate (IP3) receptors. However, it remains unknown how ER Ca 2+ release via the IP3 receptor is linked to GIIS potentiation. Recently, stromal interaction molecule (STIM) 1 was identified as a key regulator of store-operated Ca 2+ entry (SOCE), but little is known about its contribution in GPR40 signaling. We show that GPR40-mediated potentiation of GIIS is abolished by knockdown of IP3 receptor 1 (IP3R1), STIM1 or Ca 2+ -channel Orai1 in insulin-secreting MIN6 cells. STIM1 and Orai1 knockdown significantly impaired SOCE and the increase of intracellular Ca 2+ by the GPR40 agonist, fasiglifam. Furthermore, β-cell-specific STIM1 knockout mice showed impaired fasiglifam-mediated GIIS potentiation not only in isolated islets but also in vivo . These results indicate that the IP3R1/STIM1/Orai1 pathway plays an important role in GPR40-mediated SOCE initiation and GIIS potentiation in pancreatic β-cells.